Improving teacher competence through digital learning media training at Santo Fransiskus III elementary school, Jakarta - Tunjung Riski Prasetiyo; Murniati Agustian (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Learning media is one of the essential learning tools that play a crucial role in the learning process. Therefore, a teacher must be able to design and use learning media effectively. Teachers must understand the various types of learning media, as well as the advantages and disadvantages of each media. Teachers must also be able to select the appropriate learning media based on the learning objectives, subject matter, and characteristics of the students. This study aims to improve teachers' competence in using digital media at SD Santo Fransiskus III Jakarta. The participants were six teachers with various subject expertise. This study employed an action research method, consisting of two series of cycles, and examined two digital media platforms: Canva and Quizizz. The first cycle focused on enhancing teachers' digital media skills, particularly on Canva and Quizizz, to improve learner knowledge and learning outcomes. The second cycle focuses on enhancing teachers' ability to utilise digital media in the attitudinal aspects of learning. The results showed that teachers' competence in designing and applying digital media had increased after participating in this action research. This improvement is evident in the results of the teacher knowledge and skills test, as well as the observations of the learning process conducted by the teacher.